Troubling the Teacher Diversity Gap: The Perpetuation of Whiteness Through Practices of Bias Free Hiring in Ontario School Boards - Abawi, Zuhra Elizabeth (University of Toronto, Ontario Institute for Studies in Education, 2018)
Teaching staff in Ontario schools do not reflect the increasing diversity of the students who occupy Ontario classrooms today. School boards across Ontario have come under considerable scrutiny regarding the lack of diverse teacher representation that adequately reflects Ontario’s demographic composition (Childs et al., 2010; Ryan, et al., 2009; Turner, 2015). This thesis addresses the Ontario teacher diversity gap (James Turner, 2017; Turner 2015; Turner, 2014; Ryan, et al., 2009) in relation to provincial equity and inclusive educational policies, which have been created to address the dominance of white teachers in publicly-funded education in Ontario. However, findings from the research indicate that these policies have not had the desired results, and in some ways have contributed to perpetuating the status quo, and the ongoing overrepresentation of white teachers in schools. The thesis furthermore addressed the notion of bias-free hiring (Fine Handlesman, 2012; Hassouneh, 2013) practices through narratives of Ontario teachers themselves. The predominant assumption of bias-free hiring is that one can divorce themselves from their unconscious biases and preconceptions of groups who are dissimilar to them in order to recruit the so-called “most qualified applicant”. The narrative of the “most qualified applicant” is a term invoked when racialized people seek access to employment opportunities. School administrators have great influence on who is hired; therefore it is important for administrators to interrogate their own social locations and positions of power, and unconscious bias in terms of how they recruit teachers. Findings from the research indicate that teachers from racialized groups have different experiences when seeking employment as teachers in publicly-funded school boards in Ontario. In response to this the EHT Equity Hiring Toolkit for Ontario School Administrators has been developed to support school administrators to recruit more diverse teachers. The EHT provides a framework for school administrators to engage in antiracist praxis and action, by examining their social location, and ways that their positionality impacts the hiring decisions they make. School administrators can use the creation of the Toolkit based on the findings of the data that emerged from the research as a Creative Professional Activity (CPA). I consider this to be my contribution to the field of social justice education and leadership.